2014
DOI: 10.1103/physreva.90.062701
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of electronic excitation, ion-pair formation, and mutual neutralization in cesium-hydrogen collisions

Abstract: Inelastic cross sections for the excitation, deexcitation, ion-pair formation, and mutual neutralization processes in cesium-hydrogen collisions Cs(6s,6p,5d,7s) + H and Cs + + H − are calculated by means of the recently proposed branching-probability-current method and the recently calculated accurate ab initio adiabatic potential energies. Scattering calculations are performed in the low-energy range from 0.01 eV to 1 keV. It is shown that among the endothermic processes, the highest values of the partial cro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 36 publications
(118 reference statements)
1
7
0
Order By: Relevance
“…The position of the avoided crossings and the nonadiabatic couplings are employed to compute theoretical partial and total cross sections by means of the multichannel Landau-Zener approach. This method is known to be particularly well suited for processes such as the mutual neutralization reaction in which the attractive PEC of the entrance channel crosses a series of PECs corresponding to the neutral fragments, with results in good agreement with fully quantum-mechanical calculations (Yakovleva et al 2016;Hedberg et al 2014;Barklem 2017;Belyaev et al 2012;Belyaev 2013;Belyaev et al 2014b;Barklem 2016b;Mitrushchenkov et al 2017;Belyaev et al 2014a).…”
Section: Nuclear Dynamicsmentioning
confidence: 74%
See 1 more Smart Citation
“…The position of the avoided crossings and the nonadiabatic couplings are employed to compute theoretical partial and total cross sections by means of the multichannel Landau-Zener approach. This method is known to be particularly well suited for processes such as the mutual neutralization reaction in which the attractive PEC of the entrance channel crosses a series of PECs corresponding to the neutral fragments, with results in good agreement with fully quantum-mechanical calculations (Yakovleva et al 2016;Hedberg et al 2014;Barklem 2017;Belyaev et al 2012;Belyaev 2013;Belyaev et al 2014b;Barklem 2016b;Mitrushchenkov et al 2017;Belyaev et al 2014a).…”
Section: Nuclear Dynamicsmentioning
confidence: 74%
“…Recently, significant progress has been accomplished in the theoretical description of mutual neutralization both with rigorous quantum calculations (Croft et al 1999a;Guitou et al 2012;Hedberg et al 2014;Larson et al 2016;Mitrushchenkov et al 2017) or using various asymptotic models (Yakovleva et al 2016;Barklem 2017Barklem , 2016bBelyaev et al 2014a;de Ruette et al 2018), in various collision energy ranges. This includes the theoretical study of mutual neutralization between H − and several elements such as H + (Stenrup et al 2009;Nkambule et al 2016), He + (Larson et al 2016), Li + (Croft et al 1999b,a;Belyaev & Voronov 2018) (Belyaev et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…For electronic structure calculations, in addition to accurate ab initio methods, the following approximate methods have been used: the asymptotic method (Belyaev 2013a) and the Linear Combinations of Atomic Orbitals (LCAO) method (Grice & Herschbach 1974;Adelman & Herschbach 1977;Barklem 2016b). The quantum model approaches have been successfully applied to a number of low-energy inelastic processes in collisions with hydrogen: Al (Belyaev 2013a), Li, Mg, Si (Belyaev et al 2014b), Cs (Belyaev et al 2014a), Be , and Ca Barklem 2016b;Mitrushchenkov et al 2017). Comparison with the available results of quantum calculations has shown that both model approaches provide reliable collision data, especially for processes with high and moderate rate coefficients, the processes which are the most important for non-LTE modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Excitation and charge transfer in collisions of neutral atoms with hydrogen atoms are important processes in stellar atmospheres, and studies include: H + H and Be + H (Miyano Hedberg et al 2014), Mg + H , Al + H (Belyaev 2013a, Belyaev 2013b, Si + H (Belyaev et al 2014b), and Cs + H (Belyaev et al 2014a). Excitation and charge transfer in H + H + collisions have been studied (Tseliakhovich et al 2012) and proton-Rydberg atom (Vrinceanu et al 2012), atom-Rydberg atom (Srećković et al 2013) collisions studied generally.…”
Section: Atom-atom and Ion-atom Collisionsmentioning
confidence: 99%